Older Adults With Limited Literacy Are at Increased Risk for Likely Dementia - Kaup, Allison R. (Oxford University Press, 2014)
BACKGROUND. Low literacy is common among the elderly and possibly more reflective of educational attainment than years of school completed. We examined the association between literacy and risk of likely dementia in older adults. METHODS. Participants were 2,458 black and white elders (aged 71–82) from the Health, Aging and Body Composition study, who completed the Rapid Estimate of Adult Literacy in Medicine and were followed for 8 years. Participants were free of dementia at baseline; incidence of likely dementia was defined by hospital records, prescription for dementia medication, or decline in Modified Mini-Mental State Examination score. We conducted Cox proportional hazard models to evaluate the association between literacy and incidence of likely dementia. Demographics, education, income, comorbidities, lifestyle variables, and apolipoprotein E (APOE) ε4 status were included in adjusted analyses. RESULTS. Twenty-three percent of participants had limited literacy (<9th-grade level). Limited literacy, as opposed to adequate literacy (≥9th-grade level), was associated with greater incidence of likely dementia (25.5% vs17.0%; unadjusted hazard ratio [HR] = 1.75, 95% confidence interval 1.44–2.13); this association remained significant after adjustment. There was a trend for an interaction between literacy and APOE ε4 status (p = .07); the association between limited literacy and greater incidence of likely dementia was strong among ε4 noncarriers (unadjusted HR = 1.85) but nonsignificant among ε4 carriers (unadjusted HR = 1.25). CONCLUSIONS. Limited literacy is an important risk factor for likely dementia, especially among APOE ε4-negative older adults, and may prove fruitful to target in interventions aimed at reducing dementia risk.